IDENTIFIKASI VEGETASI HUTAN MELALUI DIGESTA RUMEN ANOA DI HUTAN TOMPU-RARANGGONAU DAN HUTAN DUNGI DUNGI TAMAN NASIONAL LORE LINDU - Moh. Basri (Agroland: Jurnal Ilmu-ilmu Pertanian, 2009)
The research aimed to identify types of forest vegetation found in anoa rumen dygesta which inhabit Tompu-Rararanggonau forest and Dungi Dungi Forest of Nasional Park using a Dygesta analysis method. The results of identification showed that there were five different types of vegetation found in the anoa rumen dygesta: pokae fruits (Ficus vasculosa Rump), pakis leaves (Scleria purpurescens), beringin shoots (Ficus sp.), knife grass (Panicum sp.) and kolonjono grass (Brachiaria mutica) which were in the proportion range of 51- 78%. The other kinds of vegetation found were Spinach (Ipomea aquatica Fordk), katimba shoots (Zingiber officianate Rose), banana leaves/shoots (Musa sp.), rock plant leaves and alang-alang leaves (Imperata cylindrica) which were in the proportion range of17 - 36%.